Physiological effects of cymothoid parasitization in the fish host Pomatoschistus microps (Krøyer, 1838) under increasing ocean temperatures - Cereja, Rui (2020)
Currently, the effects of global warming on marine organisms are widely recognized by the scientific community. However, studies that relate the increase in ocean temperature with other stress factors are still scarce. The main aim of this study was to evaluate the effects of water temperature increase on the parasite Anilocra frontalis, the parasite’s effects over its host Pomatoschistus microps. Therefore, P. microps were subjected to A. frontalis parasitization and both species were then exposed to two different temperatures, 22 °C (control) and 26 °C (experimental temperature). Critical Thermal Maxima (CTMax), antioxidant enzyme activity (glutathione-S-transferase, catalase and superoxide dismutase), Heat Shock Protein 70 and Lipid peroxidation (MDA content) were analysed for both species. Anilocra frontalis CTMax raised 1 °C between animals acclimated to 22 and acclimated at 26 °C (CTMax was 32 °C in animals acclimated to 22 °C and 33 °C in animals acclimated to 26 °C). Additionally, the parasites acclimated to higher temperatures showed higher release rates from their hosts. Although the parasitization did not influence P. microps’ condition, when combined with temperature it increased fish mortality rate and stress levels. The results show that temperature only influenced HSP70 values, presenting higher levels in fish acclimated to 26 °C.